Analisis Sistem Biaya Standar Dalam Meningkatkan Efisiensi Biaya Produksi Pada PT . HARDWARE - Yunita, Irma; Sundarta, Muhamad Imam; Dali, Rahmat Mulyana (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
The purpose of this study was to analyze the standard cost system in improving the efficiency of production costs at PT. HARDWARE. Testing is done by comparing the standard production costs with actual production costs. Then it can be seen whether the implementation of this production process takes place efficiently or inefficient. Based on the calculation of the analysis that compares the standard costs with actual costs or can actually be concluded that in the production of jeans, there is a difference that benefits and is not profitable on the cost of raw materials, because the calculation of production costs in PT. HARDWARE hasn’t been done properly